The Absence of the Ombudsman in Argentina: Seven Years without Collective Representation - Basaure Miranda, Isaac Marcelo (2017)
The objective of this paper is to analyze the causes and antecedents that have contributed to the fact that, in Argentina, the office of Ombudsman remains vacant. Likewise, the normative origins of the organ are reviewed, in order to understand its value and democratic mission. In the ruling entitled Center for Studies for the Promotion of Equality and Solidarity and Others and the Ministry of Energy and Mining under Collective Protection (Centro de Estudios para la Promoción de la Igualdad y la Solidaridad y otros c/ Ministerio de Energía y Minería s/ amparo colectivo), issued on August 18, 2016, the Supreme Court of Justice of the Nation exhorted the Congress of the Nation to appoint an Ombudsman in accordance with the provisions conferred on it by article 86 of the National Constitution. The Court’s decision exposed a long-standing legal problem: the absence of an Ombudsman.